Searching for a Euro reform consensus: The perspective from Central and Eastern Europe - Sebastian Blesse; Annika Havlik; Friedrich Heinemann (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
This study explores the interests and positions of Central and Eastern European (CEE) Member States in the European Monetary Union (EMU) reform debate. Its starting point is the observation that this debate is largely dominated by contributions from the larger Western European coun-tries.
Keywords: 330